2014
DOI: 10.1186/1748-717x-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Management of persistent anal canal carcinoma after combined-modality therapy: a clinical review

Abstract: Anal canal carcinoma is a rare gastro-intestinal cancer. Radiochemotherapy is the recommended primary treatment for patients with non-metastatic carcinoma; surgery is generally reserved for persistent or recurrent disease. Follow-up and surveillance after primary treatment is paramount to classify patients in those with complete remission, persistent or progressive disease. Locally persistent disease represents a clinically significant problem and its management remains subject of some controversy.The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Furthermore, the wound disruption rate appears to be higher when radical surgery is performed within 90 days after CRT [16] . This reinforces the theory that in cases of immediate persistent disease after CRT (especially after the first sequence), continuation of a close follow-up of the patient for a minimum of 6 months after the completion of radiation is reasonable [27] . In cases of complete response after CRT, a multidisciplinary team should implement a follow-up that spans the lifetime of the patient (as 1 of our patients experienced recurrence nearly 9 years after CRT) in order to detect late recurrence (in 6% of the cases in our study) or a second cancer.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, the wound disruption rate appears to be higher when radical surgery is performed within 90 days after CRT [16] . This reinforces the theory that in cases of immediate persistent disease after CRT (especially after the first sequence), continuation of a close follow-up of the patient for a minimum of 6 months after the completion of radiation is reasonable [27] . In cases of complete response after CRT, a multidisciplinary team should implement a follow-up that spans the lifetime of the patient (as 1 of our patients experienced recurrence nearly 9 years after CRT) in order to detect late recurrence (in 6% of the cases in our study) or a second cancer.…”
Section: Discussionsupporting
confidence: 68%
“…The prognostic value of the rapidity of the clinical response to therapy has been largely proven in anal carcinoma [12,15,16] . For instance, Chapet et al [15] reported on 252 patients with anal canal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Following definitive CRT, patients were reevaluated by serial digital anorectal exploration, inguinal node palpation and anoscopy at 6-week intervals. Patients with clinical suspicion of persistent disease at 6 months underwent a biopsy, and consideration of abdominoperineal resection (APR) was recommended [12] . In case of complete clinical response, the patient continues with a regular follow-up schedule, including complete physical examination and endoanal ultrasound at 3 monthly intervals for the additional 2 years and every 6 months for subsequent years.…”
Section: Follow-upmentioning
confidence: 99%
“…Potentially curative radiochemotherapy with 5-fluorouracil and mitomycin C is considered to be the gold standard in the treatment of anal cancer. [19,20] Surgery is generally reserved for persistent or recurrent cases. In our case, chemotherapy was with held due to the renal malfunction.…”
Section: Discussionmentioning
confidence: 99%